Fictions of state : culture and credit in Britain, 1694-1994 - Brantlinger, Patrick (Cornell University Press, 1996)
In this ambitious book, Patrick Brantlinger offers a cultural history of Great Britain focused on the concept of "public credit," from the 1694 founding of the Bank of England to the present. He draws on literary texts ranging from Augustan satire such as Gulliver's Travels to postmodern satire such as Martin Amis's Money: A Suicide Note. All critique the misrecognition of public credit as wealth.